THE ROLE OF ENVIRONMENTAL ASSURANCE IN THE RELATIONSHIP BETWEEN BOARD CHARACTERISTICS AND ENVIRONMENTAL DISCLOSURE - Febrianti, Agita Dini; Sari, Maylia Pramono (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2026)
This study analyzes the influence of board characteristics on environmental disclosure and examines the role of environmental assurance in moderating this influence in non-financial enterprises in Southeast Asia during 2020-2024, using panel data regression with a Fixed-Effects Model. Environmental disclosures are measured through Refinitiv ESG's environmental pillar score, while board characteristics are represented by board size, board independence, and board gender diversity. The results showed that board gender diversity had a positive and significant impact on environmental disclosure, whereas board size and board independence did not. Environmental assurance significantly moderates the relationship, attenuating the influences of board size and gender diversity on environmental disclosure. This study contributes to the corporate governance and environmental disclosure literature by providing empirical evidence that assurance does not amplify governance-driven disclosure incentives; instead, it addresses legitimacy challenges and safeguards corporate reputation, rather than expanding environmental reporting. Regulators and standard-setters should consider that environmental assurance moderates the influence of board gender diversity on environmental disclosure. The findings suggest that assurance does not amplify governance-driven disclosure incentives, suggesting that assurance may primarily serve a legitimacy-oriented function rather than directly expanding environmental disclosure.